Pengembangan Potensi Desa dan Mie Jagung (Zea mays) di Desa Karangasem, Paliyan, Gunung Kidul - Ernaningsih, Zeny (Jurnal Atma Inovasia, 2021)
Community service is one of the goals of researcher education in higher education. This service program chose Karangasem Village, Paliyan District, Gunungkidul Regency to provide innovation to develop the potential that exists in the village through a work program carried out by researchers. The method used in this research is observation through the official village website and also with the documentation method through taking pictures and videos because the situation does not allow it to come to the field. The result of this research is that researchers can provide product innovation in the form of corn noodles that can be developed by the village community into a product that is more value-added and can be traded. In addition, it also explores the potentials that exist in the village in the form of nature and culture so that it can be developed. With this program, researchers can apply the knowledge they have learned by providing community service.